Ganoderma Lucidum Triterpenoids Improve Maternal Separation-Induced Anxiety- and Depression-like Behaviors in Mice by Mitigating Inflammation in the Periphery and Brain - Mi, Xue; Zeng, Gui-Rong; Liu, Jie-Qing; Luo, Zhou-Song; Zhang, Ling; Dai, Xiao-Man; Fang, Wen-Ting; Zhang, Jing; Chen, Xiao-Chun (Nutrients, 2022)
Although early life stress (ELS) can increase susceptibility to adulthood psychiatric disorders and produce a greater inflammatory response in a stressful event, targeted preventive and therapeutic drugs still remain scarce. Ganoderma lucidum triterpenoids (GLTs) can exert anti-inflammatory effects in the periphery and central nervous systems. This study employed a combined model of “childhood maternal separation + adulthood sub-stress” to explore whether GLTs may alleviate anxiety- and depression-like behaviors in male and female mice by mitigating inflammation. Male and female pups were separated from their mothers for four hours per day from postnatal day 1 (PND 1) to PND 21; starting from PND 56, GLTs were administered intraperitoneally once daily for three weeks and followed by three days of sub-stress. Results showed that maternal separation increased the anxiety- and depression-like behaviors in both male and female mice, which disappeared after the preemptive GLTs treatment (40 mg/kg) before adulthood sub-stress. Maternal separation up-regulated the pro-inflammatory markers in the periphery and brain, and activated microglia in the prefrontal cortex and hippocampus. All the abnormalities were reversed by GLTs administration, with no adverse effects on immune organ indices, liver, and renal function. Our findings suggest that GLTs can be a promising candidate in treating ELS-induced psychiatric disorders.